Perceived Risk and the Marginal Value of Safety - Gegax, Douglas; Gerking, Shelby; Schulze, William (The Review of Economics and Statistics, 1991)
Two contributions are made toward understanding variation in marginal value of safety estimates from labor-market studies. First, marginal safety values are obtained from direct measurement of workers' perceived job-related accidental death rates. Second, wage-risk relationships are explored for several categories of workers using the hedonic price method. Statistically significant relationships found for unionized, blue collar, and blue collar-unionized workers imply marginal safety values of 1.5, 1.18, and 2.10 million dollars, respectively. Further results in this paper suggest that alternative methods are needed to measure marginal safety values for workers in other categories. Copyright 1991 by MIT Press.